Strategic alliances and product development in high technology new firms: The moderating effect of technological capabilities - Haeussler, Carolin; Patzelt, Holger; Zahra, Shaker A. (Journal of Business Venturing, 2012)
Abstract High technology new firms have extensively used strategic alliances to gain access to knowledge, resources and capabilities. However, given their inexperience and limited resources, these firms are vulnerable to their more established partners' potential opportunism. This raises the question: How can new firms maximize the benefits of these alliances while reducing their risks? In this study, we address this question by drawing upon the capabilities perspective to propose that the impact of upstream, horizontal, and downstream alliances on product development depends on the degree of specialization of new firms' technological capabilities. Using a database of biotechnology firms, the results support this argument even when different types of strategic alliances are considered.